STUDY OF OLIGO CHITOSAN IN EFFORTS TO IMPROVE THE GROWTH QUALITY OF SHALLOT (Allium ascalonicum L.) - Sugeng Priyanto; Sumarwoto Sumarwoto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
This research is intended to answer the obstacles in the cultivation techniques of shallots, especially in overcoming the low quality of growth, which in turn affects the yield and production of onions. In this experiment, spraying three types of frequency and four kinds of oligo-chitosan concentrations was tried throughout the growing onion period. Oligo-chitosan as a supplement, is given to the onion plants periodically, in various concentrations, in three different types of oligo-chitosan spraying, which they are (F1) given to plants aged 15 DAP and 45 DAP; (F2) given to plants aged 15 DAP, 30 DAP, and 45 DAP; and (F3) given to plants aged 15 DAP, 25 DAP, 35 DAP, 45 DAP. The oligo-chitosan concentration consists of four kinds of concentration, consisting of 0 ‰ (K0) as a control, 1 ‰ (K1), 2 ‰ (K2) and 3 ‰ (K3). The experiment was carried out in the field using a polybag, with a completely randomized environmental design with a 95% accuracy level. To determine the effect of treatment on the quality of growth of shallots, diversity analysis was carried out. From preliminary observations, it shows that the onion bulb growing power as a seed is quite good, while the treatment using oligochitosan gives significant results on increasing plant vigor, compared to not using oligochitosan. As for further observations that at plant height, the number of leaves and the number of tillers up to 50 days after planting, although it does not show any real effect of the treatment that was tried, but it can be suspected that the more frequency treatment given oligo-chitosan, more gives a better chance of yield than a few frequencies, while an oligo-chitosan concentration of 1 ‰ is sufficient to improve the quality of plant growth, then it can be expected that F2K1 will give higher tuber yields.Keyword: shallot, oligo-chitosan spraying frequency, oligo-chitosan concentration